2016
DOI: 10.1016/j.schres.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal auditory pattern perception in schizophrenia

Abstract: Mismatch negativity (MMN) in response to deviation from physical sound parameters (e.g., pitch, duration) is reduced in individuals with long-term schizophrenia (Sz), suggesting deficits in deviance detection. However, MMN can appear at several time intervals as part of deviance detection. Understanding which part of the processing stream is abnormal in Sz is crucial for understanding MMN pathophysiology. We measured MMN to complex pattern deviants, which have been shown to produce multiple MMNs in healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 26 publications
(30 reference statements)
3
35
0
Order By: Relevance
“…A missing tone amongst standard groups of six tones produced a smaller MMN in individuals with long‐term schizophrenia (150–200 ms after the expected onset of the tone; Salisbury & McCathern, ) and in recent‐onset patients with schizophrenia (100–250 ms; Rudolph et al ., ). We measured MMN to an extra tone that violated a quantity/number grouping rule in individuals with long‐term schizophrenia (Haigh et al ., ), and found no significant differences between groups in the early MMN, but found significant reductions in the late MMN in schizophrenia (~ 350 ms after the onset of the extra tone), suggesting specific deficits in later deviance processing. This was the first study to show specific deficits in the late MMN in schizophrenia, and it is possible that the late MMN may be more sensitive to deficits in complex deviance detection.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…A missing tone amongst standard groups of six tones produced a smaller MMN in individuals with long‐term schizophrenia (150–200 ms after the expected onset of the tone; Salisbury & McCathern, ) and in recent‐onset patients with schizophrenia (100–250 ms; Rudolph et al ., ). We measured MMN to an extra tone that violated a quantity/number grouping rule in individuals with long‐term schizophrenia (Haigh et al ., ), and found no significant differences between groups in the early MMN, but found significant reductions in the late MMN in schizophrenia (~ 350 ms after the onset of the extra tone), suggesting specific deficits in later deviance processing. This was the first study to show specific deficits in the late MMN in schizophrenia, and it is possible that the late MMN may be more sensitive to deficits in complex deviance detection.…”
Section: Introductionmentioning
confidence: 74%
“…The peak amplitude of all three MMNs was maximal over frontocentral areas and exhibited CSDs consistent with bilateral sources from temporal lobe, although source modelling was not performed. The complex MMN tasks generated both an early (~ 125 ms) and a late MMN (~ 500 ms), while the simple pitch MMN task only generated an early MMN (~ 125 ms), consistent with previous studies (Korpilahti et al ., ; Zachau et al ., ; Recasens et al ., ; Haigh et al ., ; Korpilahti et al ., ). The results shown here demonstrate that while the early MMN responses on complex pattern tasks appear to be within normal limits in Sz, the later (and in HC, the most prominent) MMN is deficient in Sz.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia diagnosis was based on the Structured Clinical Interview for DSM-IV (SCID-P). Symptom scales, neuropsychological tests, and surveys were identical to those used by Haigh et al (2016) (Table 1). All subjects had normal hearing as assessed by audiometry and were paid for participation.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that a deviance-related negative ERP can be elicited by adding an extra tone to a predictable 5-stimulus group, further suggesting that MMN is distinct from RS (Haigh et al 2016). Incidentally, this type of paradigm affords the opportunity to investigate the questions raised above, as identical tones were repeated with the same physical parameters commonly used in MMN research.…”
Section: Introductionmentioning
confidence: 97%
“…MMN to duration deviants is a particularly strong candidate biomarker of schizophrenia (Erickson et al, 2016). Other more complex paradigms with double deviants (Perez et al, 2014), tone omission deviants (Salisbury and McCathern, 2016) and pattern violations (Haigh et al, 2016b) have also demonstrated significant attenuation in MMN in patients with schizophrenia and individuals at high-risk. A more recent meta-analysis reported that the magnitude of attenuation in MMN in schizophrenia patients to complex paradigms are as large as that in simple paradigms and therefore suggest that pitch and duration paradigms provide simpler avenues for further research (Avissar, 2018).…”
Section: Introductionmentioning
confidence: 99%